Line follower balbot - Tan, Piow Yon (2010)
This project focuses on the development of a line follower algorithm for a Balbot. In this project, ATMEGA32 is chosen as the brain board controller to react towards the data received from Balance Processor Chip on the balance board which monitoring the changing of the environment through two infra-red distance sensor to solve the inclination angle problem. Hence, the system will immediately restore to the set point (balance position) through the implementation of internal PID algorithms at the balance board. Application of infra-red light sensors with the PID control is vital, in order to develop a smooth line follower robot. As a result of combination between line follower program and internal self balancing algorithms, we able to develop a dynamically stabilized Balbot with line follower function.